Factor structure models for the Post-Concussion Syndrome Scale with monolingual Spanish-speaking adults from Colombia. (19th September 2019) - Kim, Stella H.; Olabarrieta-Landa, Laiene; Gilboa-Fried, Sagit; Olivera, Silvia Leonor; Tangarife, Ricardo Valdivia; Strutt, Adriana M.; Arango-Lasprilla, Juan Carlos
ABSTRACT: Primary Objective: The Post-Concussion Syndrome Scale (PCSS) is a self-report questionnaire that measures post-concussive symptom severity and has been primarily normed on young Caucasian samples. This study aims to explore the factor structure models of a Spanish translation of the PCSS at a chronic post-traumatic brain injury (TBI) time point. Research Design: Descriptive and exploratory research designs were utilized. Methods and Procedures: The study consisted of a monolingual sample of Spanish-speaking adults from Colombia, with 100 subjects in the control group and 70 subjects in the TBI group. A t-test, chi-square, and MANOVA were calculated to compare group differences. Cronbach's alpha was calculated to investigate reliability. Confirmatory factor analysis compared item loadings onto an existing four-factor model. Exploratory factor analysis sought to identify a new factor model if the loadings did not fit. Main Outcomes and Results: There were no group differences in demographic variables. Internal consistency was acceptable. Model fit indices revealed a poor fit with the original four factors. Item loadings revealed a novel six-structure model. Conclusions: While the PCSS appears to capture general post-TBI sequelae, the underlying factors may differ due to cultural and linguistic differences in Spanish-speaking individuals. Clinical implications and future directions are further discussed.